(untitled) - Stauffer, H. Brooke (Boston, 2007)
Noted for his expertise in electrical code, author Brooke Stauffer has written a book for students and apprentices that presents authoritative coverage and explanation of NEC's 2005 requirements. This concise volume covers all aspects of residential wiring, including special systems and old work. The text is ideal for those who want the essentials of house wiring presented in a readable, well-illustrated format. Extensive coverage of safety is integrated throughout the book. NEC terms are carefully explained, and NEC Definitions are listed in the back of the book for easy reference
Keywords: Electric wiring, Interior,Dwellings,Hệ thống dây diện (nội thất),Nhà ở; Electric equipment,Thiết bị điện